Pseudotyping Lentiviral Vectors: When the Clothes Make the Virus - Alexis Duvergé; Matteo Negroni (Viruses, 2020)
Delivering transgenes to human cells through transduction with viral vectors constitutes one of the most encouraging approaches in gene therapy. Lentivirus-derived vectors are among the most promising vectors for these approaches. When the genetic modification of the cell must be performed in vivo, efficient specific transduction of the cell targets of the therapy in the absence of off-targeting constitutes the Holy Grail of gene therapy. For viral therapy, this is largely determined by the characteristics of the surface proteins carried by the vector. In this regard, an important property of lentiviral vectors is the possibility of being pseudotyped by envelopes of other viruses, widening the panel of proteins with which they can be armed. Here, we discuss how this is achieved at the molecular level and what the properties and the potentialities of the different envelope proteins that can be used for pseudotyping these vectors are.